A Co2P-coated hollow carbon sphere composite material for sodium ion battery negative electrode material and preparation method thereof

Through the preparation of Co2P-coated hollow carbon ball composite material, the challenges of sodium ion battery anode material in capacity, cycle life and rate performance are solved, and efficient and stable sodium storage performance and excellent electrochemical performance are achieved.

CN119528097BActive Publication Date: 2025-03-25JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510089092.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-25
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Sodium ion batteries have challenges in capacity, cycle life and rate performance. The existing transition metal compounds and carbon materials are structurally unstable during high temperature pyrolysis and ion insertion, resulting in limited performance.

Method used

The Co2P coated hollow carbon sphere composite material is used as the negative electrode material for sodium ion batteries. This material is prepared by a simple two-step hydrothermal method. The Co2P nanophase is dispersed on the hollow carbon sphere to form a multi-stage hollow structure.

Benefits of technology

It achieves excellent performance such as long life, high capacity, and high magnification. The Co2P phase improves sodium storage performance, the hollow carbon sphere enhances conductivity and stability, and synergistically alleviates volume expansion and significantly improves the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528097B_ABST
    Figure CN119528097B_ABST
Patent Text Reader

Abstract

The invention discloses a Co2P-coated hollow carbon ball composite material for a sodium ion battery negative electrode material and a preparation method thereof, and relates to the technical field of electrochemical energy storage materials. Firstly, glucose, P123 and sodium oleate are dissolved in deionized water to obtain a pre-spheroidizing precursor solution; the pre-spheroidizing precursor solution is placed in a reactor for hydrothermal treatment to finally obtain a pre-carbonized carbon ball material; cobalt nitrate hexahydrate and 2-methylimidazole are respectively dissolved in a DMF solution, and mixed with the pre-carbonized carbon ball material to obtain a mixed solution of a carbon ball material having a zeolite imidazole skeleton; the mixed solution of the carbon ball material having a zeolite imidazole skeleton is placed in a reactor for hydrothermal treatment to finally obtain a pre-carbonized carbon ball material having a zeolite imidazole skeleton; the pre-carbonized carbon ball material having a zeolite imidazole skeleton and sodium hypophosphite are placed in a tubular furnace, and carbonization and phosphating treatment are simultaneously performed in an inert gas atmosphere to obtain the Co2P-coated hollow carbon ball composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage materials, and in particular to a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery and a preparation method thereof. Background Art

[0002] As the energy crisis and environmental problems intensify, the demand for efficient energy storage technology is becoming increasingly urgent. Lithium-ion batteries (LIBs) are widely used in portable electronic products and electric vehicles. However, with the limited resources of lithium ore and the rising cost year by year, an effective alternative is urgently needed. At the same time, sodium-ion batteries (SIBs) have great potential for large-scale energy storage due to their abundant resources and cost-effectiveness. However, the larger size and heavier mass of sodium ions make sodium-ion batteries face challenges in capacity, cycle life and rate performance. Therefore, the development of efficient and stable negative electrode materials has become one of the key tasks for the widespread application of sodium-ion batteries.

[0003] Transition metal compounds, especially phosphides, have great potential as anode materials for sodium-ion batteries due to their good conversion reactions, high theoretical capacity, low redox potential and excellent electrochemical reversibility. However, they still suffer from large volume changes and low intrinsic conductivity, which leads to rapid capacity decay and poor rate performance during cycling.

[0004] Metal-organic frameworks (MOFs) are carbon skeleton structures formed by self-assembly of metal ions and organic ligands. They have the advantages of tunable composition, rich porous structure and diverse reaction sites. MOFs with imidazole as organic ligands, such as ZIF, have attracted much attention due to their natural advantage of nitrogen doping. Among them, cobalt-based metal compounds derived from ZIF-67 generally exhibit excellent conductivity and good electrochemical stability. However, the structure of traditional MOF materials is prone to decomposition during high-temperature pyrolysis, making it difficult to maintain its unique morphology, and the pure MOF crystal structure is prone to collapse during ion insertion and separation, limiting the further improvement of its electrochemical performance.

[0005] Carbon materials (especially hard carbon) as negative electrode materials for sodium ion batteries have formed relatively mature industrial technologies in many fields. The hollow carbon sphere material prepared by the template method has excellent cycle stability due to its excellent hollow structure carbon, but its theoretical capacity is relatively low.

[0006] Therefore, it is necessary to carry out reasonable structural design of transition metal compounds and carbon materials. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the existing technology and provide a Co2P-coated hollow carbon sphere composite material for sodium ion battery negative electrode material and a preparation method thereof. The Co2P-coated hollow carbon sphere composite material prepared by the method provided by the present invention has excellent properties such as long life, high capacity, and high rate, and the raw materials are low in price and widely available, and the preparation method is simple and efficient.

[0008] A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery comprises the following steps:

[0009] Step 1: Dissolve glucose, P123 and sodium oleate in deionized water, stir and mix thoroughly, and stand to defoam to obtain a pre-spheroidizing precursor solution;

[0010] Step 2: placing the pre-spheroidized precursor solution obtained in step 1 in a reaction kettle, subjecting it to hydrothermal treatment in an oven, cooling it to room temperature, centrifugally precipitating it, washing it, and drying it in sequence to obtain a pre-carbonized carbon sphere material;

[0011] Step 3: Dissolve cobalt nitrate hexahydrate and 2-methylimidazole in DMF solution respectively, stir evenly, and obtain solution A and solution B respectively; mix the pre-carbonized carbon sphere material obtained in step 2 with solution A to obtain a mixed solution C; ultrasonicate the mixed solution C until the solute is evenly dispersed; then transfer solution B to the mixed solution C; and stir to obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton;

[0012] Step 4: placing the mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 in a reaction kettle, performing hydrothermal treatment in an oven, cooling to room temperature, centrifuging, precipitating, washing and drying in sequence to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton;

[0013] Step 5: placing the pre-carbonized carbon ball material with a zeolite imidazole skeleton obtained in step 4 and sodium hypophosphite in a tube furnace, and simultaneously performing carbonization and phosphating treatment under an inert gas atmosphere, and after cooling to room temperature, obtaining a Co2P-coated hollow carbon ball composite material;

[0014] In the Co2P-coated hollow carbon sphere composite material, the particle size of the Co2P nanophase is 20nm-30nm; the diameter of the hollow carbon sphere is 500nm-600nm.

[0015] Preferably, in the step 1, the glucose, P123 and sodium oleate are fully stirred for 30 to 60 minutes, and the defoaming time is 2 to 3 hours.

[0016] Preferably, in step 1, the dosage ratio of glucose to deionized water is 4-5 g:80-100 ml; the weight ratio of glucose, P123, and sodium oleate is 15:0.1-0.2:0.02-0.03.

[0017] Preferably, the hydrothermal treatment in step 2 is performed for 12 to 24 hours at a hydrothermal temperature of 160 to 180° C., washed with deionized water for multiple times, and dried at 60 to 80° C. for 10 hours.

[0018] Preferably, the pre-carbonized carbon sphere material in step 3 is added to solution A and ultrasonically dispersed for 15 to 30 minutes;

[0019] The solution B is transferred to the mixed solution C, and after stirring for 30 to 60 minutes, a mixed solution of carbon sphere material having a zeolite imidazole skeleton is obtained.

[0020] Preferably, in the step three, the mass ratio of the pre-carbonized carbon ball material to cobalt nitrate hexahydrate is 2-4:8-9, the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:1-4, and the amount ratio of the pre-carbonized carbon ball material to the DMF solution is 0.1-0.4 g:30-120 ml.

[0021] Preferably, the carbon sphere material with a zeolite imidazole skeleton in step 4 is hydrothermally treated in an oven for 12 to 24 hours at a hydrothermal temperature of 160 to 180° C., washed with ethanol multiple times, and dried at 60 to 80° C. for 10 hours.

[0022] Preferably, the carbonization treatment in step 5 is carried out in an argon or nitrogen atmosphere, the carbonization temperature is 400-600° C., the heating rate is 1-2° C. / min, and the carbonization time is 1-3 hours;

[0023] In the step 5, the mass ratio of the pre-carbonized carbon ball material having a zeolite imidazole skeleton to the sodium hypophosphite is 1:4-10.

[0024] Preferably, the sodium hypophosphite in step five is placed in a porcelain boat, which is located at the upstream end of the tubular furnace air inlet, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is located at the downstream end of the tubular furnace air inlet. The heating rate is controlled at 1 to 2°C / min. A low heating rate is a key step for successful phosphating.

[0025] A Co2P-coated hollow carbon sphere composite material for a sodium ion battery negative electrode material is prepared by a preparation method of the Co2P-coated hollow carbon sphere composite material for a sodium ion battery negative electrode material.

[0026] Beneficial effects of the present invention:

[0027] The present invention adopts a simple two-step hydrothermal method to prepare a Co2P-coated hollow carbon sphere composite material with high efficiency and stable sodium storage, wherein Co2P nanoparticles are dispersed on the hollow carbon spheres. Experimental results show that the composite material has a unique multi-level hollow structure, wherein the Co2P phase improves the sodium storage performance of the material, and the hollow carbon spheres help to enhance the conductivity and stability. At the same time, the synergistic effect of the external Co2P phase and the internal hollow carbon spheres can effectively alleviate the volume expansion of the Co2P phase during the cycle, so that the composite material has excellent properties such as long life and high capacity.

[0028] The composite material prepared by the present invention can not only significantly improve the overall conductivity and mechanical strength of the electrode, but also have higher stability and reliability throughout the entire charge and discharge cycle. At the same time, its high specific surface area, low density, good structural stability and short ion transmission path also give the composite material better electrochemical performance. Hollow carbon spheres have excellent conductivity and volume buffering capacity, while transition metal compounds (Co2P) exhibit good electrochemical properties. The combination of the two can effectively complement each other, thereby significantly improving the overall performance of the material. This design idea provides an important reference for the development of high-efficiency negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the pre-carbonized carbon sphere material obtained in Example 1 after carbonization at 600 degrees;

[0030] Figure 2 This is a scanning electron microscope image of the Co2P-coated hollow carbon sphere composite material prepared in Example 1;

[0031] Figure 3 This is a scanning electron microscope image of the Co2P-coated hollow carbon sphere composite material prepared in Example 2;

[0032] Figure 4 This is a scanning electron microscope image of the Co2P-coated hollow carbon sphere composite material prepared in Example 3;

[0033] Figure 5 This is a scanning electron microscope image of the Co2P-coated hollow carbon sphere composite material prepared in Example 4;

[0034] Figure 6 This is a scanning electron microscope image of the Co2P-coated hollow carbon sphere composite material prepared in Example 5;

[0035] Figure 7 The cycling performance curve of the Co2P-coated hollow carbon sphere composite material prepared in Example 3 at a current density of 0.2C;

[0036] Figure 8The figure is a rate performance curve of the Co2P-coated hollow carbon sphere composite material prepared in Example 4 at a current density of 0.2C to 5C;

[0037] Fig. 9 The XRD (X-ray diffraction) diagram of the Co2P-coated hollow carbon sphere composite material prepared in Example 3;

[0038] Fig.10 This is the EDS (energy dispersive spectrum analysis) diagram of the Co2P-coated hollow carbon sphere composite material prepared in Example 3. DETAILED DESCRIPTION

[0039] In order to better and more comprehensively understand the present invention, the present invention is described in more detail below according to the relevant drawings. Several preferred embodiments of the present invention are given in the drawings. However, the embodiments are only further detailed descriptions of the present invention and do not limit the scope of the present invention. The purpose of providing these embodiments is to promote a more thorough and comprehensive understanding of the contents disclosed in the present invention.

[0040] Embodiment 1 of the present invention:

[0041] A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery comprises the following steps:

[0042] Step 1: Dissolve 4 g of glucose, 0.0063 g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and 0.046 g of sodium oleate in 80 ml of deionized water, stir for 30 min, and then stand for 2 hours to defoam to obtain a pre-spheroidizing precursor solution;

[0043] Step 2: Place the pre-spheroidized precursor solution obtained in step 1 in a 100 ml reactor, react at 160° C. in an oven for 24 hours, cool to room temperature, centrifuge to obtain a precipitate, wash with deionized water for multiple times, and dry at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material;

[0044] Step 3: Take 0.873g of 3mmol cobalt nitrate hexahydrate and 0.246g of 3mmol 2-methylimidazole and dissolve them in 30ml DMF solution respectively, stir evenly, and obtain solution A and solution B respectively, then take 0.4g of the pre-carbonized carbon sphere material obtained in the step 2 and mix it with solution A to obtain a mixed solution C, after the mixed solution C is ultrasonicated for 20min until the solute is evenly dispersed, transfer solution B to the mixed solution C, stir for 30min, and obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton;

[0045] Step 4: The mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 is transferred into a 100 ml reactor, reacted at 160° C. in an oven for 12 hours, cooled to room temperature and centrifuged to obtain a precipitate, washed with ethanol several times, and dried at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton;

[0046] Step 5: Transfer 0.1 g of pre-carbonized carbon ball material with a zeolite imidazole skeleton and 0.4 g of sodium hypophosphite to two porcelain boats and place them in a tubular furnace, wherein the sodium hypophosphite is placed upstream of the air inlet of the tubular furnace, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is placed downstream of the air outlet of the tubular furnace. In a nitrogen atmosphere, heat the temperature from room temperature to 600 degrees Celsius at a rate of 2°C / min and keep it for 2 hours. After cooling to room temperature, a Co2P-coated hollow carbon ball composite material is obtained.

[0047] Embodiment 2 of the present invention:

[0048] A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery comprises the following steps:

[0049] Step 1: Dissolve 4 g of glucose, 0.0063 g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and 0.046 g of sodium oleate in 80 ml of deionized water, stir for 30 min, and then stand for 2 hours to defoam to obtain a pre-spheroidizing precursor solution;

[0050] Step 2: Place the pre-spheroidized precursor solution obtained in step 1 in a 100 ml reactor, react at 160° C. in an oven for 24 hours, cool to room temperature, centrifuge to obtain a precipitate, wash with deionized water for multiple times, and dry at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material;

[0051] Step 3: Take 0.873g of 3mmol cobalt nitrate hexahydrate and 0.246g of 3mmol 2-methylimidazole and dissolve them in 30ml DMF solution respectively, stir evenly, and obtain solution A and solution B respectively, then take 0.3g of the pre-carbonized carbon sphere material obtained in step 2 and mix it with solution A to obtain a mixed solution C, after the mixed solution C is ultrasonicated for 20min and the solute is in a uniformly dispersed state, the solution B is transferred to the mixed solution C, and stirred for 30min to obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton;

[0052] Step 4: The mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 is transferred into a 100 ml reactor, reacted at 160° C. in an oven for 12 hours, cooled to room temperature and centrifuged to obtain a precipitate, washed with ethanol several times, and dried at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton;

[0053] Step 5: Transfer 0.1 g of pre-carbonized carbon ball material with a zeolite imidazole skeleton and 0.4 g of sodium hypophosphite to two porcelain boats and place them in a tubular furnace, wherein the sodium hypophosphite is placed upstream of the air inlet of the tubular furnace, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is placed downstream of the air outlet of the tubular furnace. In a nitrogen atmosphere, heat the temperature from room temperature to 600 degrees Celsius at a rate of 2°C / min and keep it for 2 hours. After cooling to room temperature, a Co2P-coated hollow carbon ball composite material is obtained.

[0054] Embodiment 3 of the present invention:

[0055] A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery comprises the following steps:

[0056] Step 1: Dissolve 4 g of glucose, 0.0063 g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and 0.046 g of sodium oleate in 80 ml of deionized water, stir for 30 min, and then stand for 2 hours to defoam to obtain a pre-spheroidizing precursor solution;

[0057] Step 2: Place the pre-spheroidized precursor solution obtained in step 1 in a 100 ml reactor, react at 160° C. in an oven for 24 hours, cool to room temperature, centrifuge to obtain a precipitate, wash with deionized water for multiple times, and dry at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material;

[0058] Step 3: Take 0.873g of 3mmol cobalt nitrate hexahydrate and 0.246g of 3mmol 2-methylimidazole and dissolve them in 30ml DMF solution respectively, stir evenly, and obtain solution A and solution B respectively, then take 0.2g of the pre-carbonized carbon sphere material obtained in step 2 and mix it with solution A to obtain a mixed solution C, after the mixed solution C is ultrasonicated for 20min until the solute is evenly dispersed, transfer solution B to the mixed solution C, stir for 30min, and obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton;

[0059] Step 4: The mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 is transferred into a 100 ml reactor, reacted at 160° C. in an oven for 12 hours, cooled to room temperature and centrifuged to obtain a precipitate, washed with ethanol several times, and dried at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton;

[0060] Step 5: Transfer 0.1 g of pre-carbonized carbon ball material with a zeolite imidazole skeleton and 0.4 g of sodium hypophosphite to two porcelain boats and place them in a tubular furnace, wherein the sodium hypophosphite is placed upstream of the air inlet of the tubular furnace, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is placed downstream of the air outlet of the tubular furnace. In a nitrogen atmosphere, heat the temperature from room temperature to 600 degrees Celsius at a rate of 2°C / min and keep it for 2 hours. After cooling to room temperature, a Co2P-coated hollow carbon ball composite material is obtained.

[0061] The Co2P-coated hollow carbon sphere composite material prepared in Example 3 was used as the carbon material, and then the carbon material was evenly mixed with acetylene black and PVDF in a mass ratio of 8:1:1, and then appropriate NMP was added to the mixture and stirred for 6 hours to form a uniform slurry and evenly coated on the copper foil, and dried at 80°C in a vacuum drying oven for 12 hours. After drying, the copper foil was punched into a disc with a diameter of 12 mm, and a metal sodium sheet was used as a counter electrode, and assembled in a CR2032 type button-type sodium ion battery, the glass fiber membrane was (Whatman GF / D) diaphragm, and the electrolyte used was 1 mol·L −1 The battery was assembled in an argon-protected glove box using a mixed solution of NaClO4, ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1.

[0062] The electrochemical performance test was conducted on the Blue Power CT2001A multi-channel Blue Power battery test system, with a termination voltage range of 0.01V to 3.0V. The test results are as follows: Fig. 9 As shown, at a current density of 0.2C, there is still 332.3 mAhg after 200 cycles. -1 The reversible specific capacity and cycle stability are good.

[0063] Fig. 9 This is the XRD pattern of the Co2P-coated hollow carbon sphere composite material prepared in Example 3. It can be seen from the figure that there are three obvious characteristic peaks at 2θ=40.7, 2θ=43.3, and 2θ=52.0, which correspond to the peak values ​​of the standard PDF-card of Co2P (Joint Committee on Powder Diffraction Standards, JCPDS card number) 32-0306.

[0064] Fig.10 This is the EDS image of the Co2P-coated hollow carbon sphere composite material prepared in Example 3. It can be seen from the image that the distribution of Co and P elements is relatively uniform;

[0065] Comparative Examples 1 to 3 obtained in the scanning electron microscope image ( Figures 1 to 3 ), when the mass ratio of pre-carbonized carbon ball material to cobalt nitrate hexahydrate is 0.2g:0.873g, the Co2P phase is more evenly dispersed and the cycle life is long.

[0066] Embodiment 4 of the present invention:

[0067] A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery comprises the following steps:

[0068] Step 1: Dissolve 4 g of glucose, 0.0063 g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and 0.046 g of sodium oleate in 80 ml of deionized water, stir for 30 min, and then stand for 2 hours to defoam to obtain a pre-spheroidizing precursor solution;

[0069] Step 2: Place the pre-spheroidized precursor solution obtained in step 1 in a 100 ml reactor, react at 160° C. in an oven for 24 hours, cool to room temperature, centrifuge to obtain a precipitate, wash with deionized water for multiple times, and dry at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material;

[0070] Step 3: Take 0.873g of 3mmol cobalt nitrate hexahydrate and 0.492g of 6mmol 2-methylimidazole and dissolve them in 30ml DMF solution respectively, stir evenly, and obtain solution A and solution B respectively, then take 0.2g of the pre-carbonized carbon sphere material obtained in step 2 and mix it with solution A to obtain a mixed solution C, after the mixed solution C is ultrasonicated for 20min until the solute is evenly dispersed, transfer solution B to the mixed solution C, stir for 30min, and obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton;

[0071] Step 4: The mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 is transferred into a 100 ml reactor, reacted at 160° C. in an oven for 12 hours, cooled to room temperature and centrifuged to obtain a precipitate, washed with ethanol several times, and dried at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton;

[0072] Step 5: Transfer 0.1 g of pre-carbonized carbon ball material with a zeolite imidazole skeleton and 0.4 g of sodium hypophosphite to two porcelain boats and place them in a tubular furnace, wherein the sodium hypophosphite is placed upstream of the air inlet of the tubular furnace, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is placed downstream of the air outlet of the tubular furnace. In a nitrogen atmosphere, heat the temperature from room temperature to 600 degrees Celsius at a rate of 2°C / min and keep it for 2 hours. After cooling to room temperature, a Co2P-coated hollow carbon ball composite material is obtained.

[0073] The preparation of the negative electrode sheet of the sodium ion battery and the assembly of the battery are the same as those in Example 3. The test is also carried out on the Blue Power CT2001A multi-channel Blue Power battery test system. The termination voltage range is 0.01V to 3.0V. The current density of the rate performance test is 0.2C to 5C, and 10 cycles are tested at each current density; the current density of the cycle performance test is 0.2C, and 60 cycles are tested. Figure 8 It can be seen that after 60 cycles at different current densities, the reversible specific capacity of 369.3 mAh g-1 can still be maintained, showing good rate performance and cycle performance.

[0074] Embodiment 5 of the present invention:

[0075] A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery comprises the following steps:

[0076] Step 1: Dissolve 4 g of glucose, 0.0063 g of P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and 0.046 g of sodium oleate in 80 ml of deionized water, stir for 30 min, and then stand for 2 hours to defoam to obtain a pre-spheroidizing precursor solution;

[0077] Step 2: Place the pre-spheroidized precursor solution obtained in step 1 in a 100 ml reactor, react at 160° C. in an oven for 24 hours, cool to room temperature, centrifuge to obtain a precipitate, wash with deionized water for multiple times, and dry at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material;

[0078] Step 3: Take 0.873g of 3mmol cobalt nitrate hexahydrate and 0.738g of 9mmol 2-methylimidazole and dissolve them in 30ml DMF solution respectively, stir evenly, and obtain solution A and solution B respectively, then take 0.2g of the pre-carbonized carbon sphere material obtained in step 2 and mix it with solution A to obtain a mixed solution C, after the mixed solution C is ultrasonicated for 20min until the solute is evenly dispersed, transfer solution B to the mixed solution C, stir for 30min, and obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton;

[0079] Step 4: The mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 is transferred into a 100 ml reactor, reacted at 160° C. in an oven for 12 hours, cooled to room temperature and centrifuged to obtain a precipitate, washed with ethanol several times, and dried at 80° C. for 10 hours to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton;

[0080] Step 5: Transfer 0.1 g of pre-carbonized carbon ball material with a zeolite imidazole skeleton and 0.4 g of sodium hypophosphite to two porcelain boats and place them in a tubular furnace, wherein the sodium hypophosphite is placed upstream of the air inlet of the tubular furnace, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is placed downstream of the air outlet of the tubular furnace. In a nitrogen atmosphere, heat the temperature from room temperature to 600 degrees Celsius at a rate of 2°C / min and keep it for 2 hours. After cooling to room temperature, a Co2P-coated hollow carbon ball composite material is obtained.

[0081] Comparative Examples 3 to 5 obtained in the scanning electron microscope ( Figures 4 to 6 ), when the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:3, the Co2P phase is more densely dispersed, when the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:2, the rate performance is good, and when the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:1, the cycle performance is good.

[0082] The above-mentioned embodiments merely express several implementation schemes of the present invention, and the description thereof is relatively comprehensive and detailed, but it cannot be understood as limiting the scope of the invention patent, but should conform to the widest scope consistent with the principles and novel features disclosed in the present invention. It should be pointed out that, for ordinary technicians in this field, various modifications and improvements can be made under the premise of the conception of the present invention, which are all within the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery, characterized in that: The steps include: Step 1: Dissolve glucose, P123 and sodium oleate in deionized water, stir and mix thoroughly, and stand to defoam to obtain a pre-spheroidizing precursor solution; Step 2: placing the pre-spheroidized precursor solution obtained in step 1 in a reaction kettle, subjecting it to hydrothermal treatment in an oven, cooling it to room temperature, centrifugally precipitating it, washing it, and drying it in sequence to obtain a pre-carbonized carbon sphere material; Step 3: Dissolve cobalt nitrate hexahydrate and 2-methylimidazole in DMF solution respectively, stir evenly, and obtain solution A and solution B respectively; mix the pre-carbonized carbon sphere material obtained in step 2 with solution A to obtain a mixed solution C; after sonicating the mixed solution C so that the solute is evenly dispersed, transfer solution B to the mixed solution C, and stir to obtain a mixed solution of carbon sphere material having a zeolite imidazole skeleton; Step 4: placing the mixed solution of the carbon sphere material having a zeolite imidazole skeleton obtained in step 3 in a reaction kettle, performing hydrothermal treatment in an oven, cooling to room temperature, centrifuging, precipitating, washing and drying in sequence to obtain a pre-carbonized carbon sphere material having a zeolite imidazole skeleton; Step 5: placing the pre-carbonized carbon ball material with a zeolite imidazole skeleton obtained in step 4 and sodium hypophosphite in a tube furnace, and simultaneously performing carbonization and phosphating treatment under an inert gas atmosphere, and after cooling to room temperature, obtaining a Co2P-coated hollow carbon ball composite material; In the Co2P-coated hollow carbon sphere composite material, the particle size of the Co2P nanophase is 20nm-30nm; the diameter of the hollow carbon sphere is 500nm-600nm.

2. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: In the step 1, the glucose, P123 and sodium oleate are fully stirred for 30 to 60 minutes, and the defoaming time is 2 to 3 hours.

3. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: In the step 1, the dosage ratio of glucose to deionized water is 4-5 g:80-100 ml; the weight ratio of glucose, P123, and sodium oleate is 15:0.1-0.2:0.02-0.

03.

4. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: The hydrothermal treatment in step 2 is performed for 12 to 24 hours at a temperature of 160 to 180° C., and deionized water is used for multiple washings, and drying is performed at 60 to 80° C. for 10 hours.

5. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: The pre-carbonized carbon sphere material in step 3 is added to a mixed solution of cobalt nitrate hexahydrate and DMF and the ultrasonic dispersion time is 15 to 30 minutes. After adding 2-methylimidazole to the solution after ultrasonic dispersion, the stirring time is 30 to 60 minutes.

6. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: In the step 3, the mass ratio of the pre-carbonized carbon ball material to cobalt nitrate hexahydrate is 2-4:8-9, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 1:1-4, and the amount ratio of the pre-carbonized carbon ball material to the DMF solution is 0.1-0.4g:30-120ml.

7. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: In the step 4, the carbon sphere material with a zeolite imidazole skeleton is subjected to hydrothermal treatment in an oven for 12 to 24 hours at a hydrothermal temperature of 160 to 180° C., washed with ethanol multiple times, and dried at 60 to 80° C. for 10 hours.

8. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: In the step 5, the carbonization treatment is carried out in an argon or nitrogen atmosphere, the carbonization temperature is 400-600° C., the heating rate is 1-2° C. / min, and the carbonization time is 1-3 hours; In the step 5, the mass ratio of the pre-carbonized carbon ball material having a zeolite imidazole skeleton to the sodium hypophosphite is 1:4-10.

9. The method for preparing a Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery according to claim 1, characterized in that: The sodium hypophosphite in step five is placed in a porcelain boat, which is located at the upstream end of the tube furnace air inlet, and the pre-carbonized carbon ball material with a zeolite imidazole skeleton is located at the downstream end of the tube furnace air inlet, and the heating rate is controlled at 1-2°C / min.

10. A Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery, characterized in that: The Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery is prepared by the preparation method of the Co2P-coated hollow carbon sphere composite material for a negative electrode material of a sodium ion battery as claimed in claim 1.

Citation Information

Patent Citations

  • Hollow carbon material doped with hollow cobalt phosphide nanoparticles in situ, preparation method and application of hollow carbon material in catalytic electrolysis of water for hydrogen production

    CN108816258A

  • CoP@carbon nanotube composite material and preparation and application thereof

    CN111799469A